2492. Clinical, Virologic, and Immunologic Characteristics of Zika Virus Infection in a Cohort of US Patients. (26th November 2018) - El Sahly, Hana M; Gorchakov, Rodion; Murray, Kristy; Patel, Shital; Atmar, Robert L; Keitel, Wendy; Hoft, Daniel; Barrett, Jill; Bailey, Jason; Rouphael, Nadine; Edupuganti, Srilatha; Raabe, Vanessa; et al.
Abstract: Background: The clinical, virologic and immunologic characteristics of Zika virus (ZIKV) infections in US patients are poorly defined. Methods: US patients with suspected Zika virus (ZIKV) infection were enrolled and clinical data and specimens were prospectively collected. Body fluids were tested for ZIKV RNA by PCR and blood was tested using serologic and cellular immune assays. Findings from those with confirmed ZIKV infections (cases) and ZIKV-negative controls were compared. Results: We enrolled 45 cases and 14 controls. The most commonly reported symptoms among cases and controls were maculopapular rash (97.8% and 81.8%), fatigue (86.7% and 81.8%) and arthralgia (82.2% and 54.5%), respectively. The sensitivity and duration of detection by PCR were highest in whole blood samples (94% of 35 cases who had samples collected up to day 79 post illness onset were positive); strikingly, 84% of those were still positive at 65–79 days post illness onset (Figure 1). ZIKV neutralizing antibodies were detected in all cases and none of the controls, and titers were significantly higher in dengue virus (DENV)-experienced subjects than in DENV-naïve ones (Figure 2). Among cases, anti-ZIKV IgG antibodies were also significantly higher in DENV-experienced patients, while anti-ZIKV IgM antibodies were no higher in DENV-experienced compared with naïve ones. Using intracellular cytokine staining, the highest frequencies of T cells producing IFN-γ, IL-2 and/or TNF-α were against the NS1, NS3, and NS5 proteins for CD4+ T cells, and against the E, NS3, and NS5 proteins for CD8+ T cells (Figure 3). Conclusion: Detection of ZIKV RNA was more frequent and much more prolonged in whole blood samples compared with other body fluids. Diagnostic molecular assays on this easily obtained fluid should be prioritized for point-of-care development. Robust cellular responses to E, NS3 and NS5 proteins could have implications for vaccine development. Disclosures: R. L. Atmar, Takeda Vaccines, Inc.: Investigator, Research grant.